Quest for Identity: Re-Examining the Process of Federal Restructuring of the Nepali State - Mistry, Asis (Social Inquiry: Journal of Social Science Research, 2020)
The agenda of restructuring the state has been the most deliberated issue for all intellectuals, political leaders and civil society activists in Nepal. The restructuring of Nepali state became a central component of the 2006 peace deal. Federalism was, however, included in the interim constitution as a binding principle for the Constituent Assembly on the verge of violent protests in the Tarai in 2007. The fundamental question during the Maoist insurgency remained whether federalism based on ethnic affiliation will be materialized. But after the Madhesh mutiny, the question that dominated the public discourse was whether “ethnic federalism” can be materialized as a mean to achieve more inclusive, institutionalized and sustainable democratic polity in Nepal. This article re-examines the process of federal restructuring of Nepali State on the backdrop of contemporary politics of identity.